Some characteristics of deverbal nominals in Slavic and Romance languages - Matracki, Ivica Peša; Kovačić, Vinko (Linguistik Online, 2016)
In this paper we will investigate the nature of deverbal nominals across languages. Deverbal nouns are typically classified according to their word-formation model: affixation and conver-sion. Our study will compare the word formation of deverbal nominals in Slavic (Croatian, Slovenian and Polish) and Romance languages (Italian, French and Spanish) in order to show (i) that affixation corresponds to a specific mode of morphological operations and (ii) that the differences and similarities between deverbal nominals of these two language families follow from the properties of the base verbs. Furthermore, our analysis will try to shed some light on the distinction between nouns and verbs. The paper comprises three major thematic parts. The first part briefly reviews the basic notions and theoretical assumptions of Generative Grammar regarding word formation. We have especially tried to explain those notions that we draw from Distributed Morphology. This part further exposes the theoretical framework that is used in this paper. In the second part, deverbal nominals in Slavic languages are analysed and de-scribed. We primarily investigate the Slavic languages, since in these languages morphology plays a larger role in the construction of deverbal nouns. The third part contains an investiga-tion of the phrasal structure of nominalizations across the Romance languages. We close the work with a general conclusion about the behaviour of deverbal nouns in these two groups of languages. We concentrate mainly on the differences between the phrasal architecture of nom-inalizations and correspondent verbal constructions.